Some Nonlinear Integral Inequalities Connected with Retarded Terms on Time Scales. (9th December 2020) - Khan, Zareen A.; Ahmad, Hijaz; Rashid, Saima; Kaynak, Kadir; Wang, Miao-Kun
Abstract : The objective of this research is to formulate a specific class of integral inequalities of Gronwall kind concerning retarded term and nonlinear integrals with time scales theory. Our results generate several new inequalities that reflect continuous and discrete form, as well as giving the unknown function an upper bound estimate. The effectiveness of such inequalities arises from the belief that it is widely relevant in unique circumstances where there is no valid utilization of various available inequalities. Applications are additionally represented to display the legitimacy of built-up hypotheses.